High-aluminum doped cobalt carbonate as well as preparation method and application thereof

Through the segmented co-precipitation method and the use of precipitant types, the problems of uneven morphology and aluminum distribution of high-aluminum doped cobalt carbonate are solved, and the uniformity and electrical performance of high-aluminum doped cobalt carbonate are improved, which is suitable for high-performance lithium-ion battery positive electrode materials.

CN120535022APending Publication Date: 2025-08-26JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202510665799.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

It is difficult to obtain high-aluminum doped cobalt carbonate particles with good spherical shape in the prior art, resulting in poor dispersion of the material during the coating of the battery electrode sheet, affecting the uniformity and consistency of the electrode sheet. At the same time, the distribution of aluminum elements in the inside and surface of the particles is uneven, resulting in unstable electrochemical performance of the lithium cobalt oxide positive electrode material.

Method used

The segmented co-precipitation method is adopted, and the types of precipitants used for co-precipitation of each section are controlled. Through the first co-precipitation reaction and the second co-precipitation reaction, carbonate and organic weak acid solutions are used as precipitants to control the doping amount and uniformity of aluminum, avoid aluminum segregation, and form dense spherical particles.

Benefits of technology

The doping amount and uniformity of aluminum in cobalt carbonate were improved, and high-aluminum doped cobalt carbonate was obtained. The tricobalt tetroxide produced was excellent in electrical performance. The battery as the lithium cobalt oxide positive electrode material showed high first-time discharge specific capacity and good capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535022A_ABST
    Figure CN120535022A_ABST
Patent Text Reader

Abstract

The invention provides high-aluminum doped cobalt carbonate and a preparation method and application thereof, and the preparation method comprises the following steps: (1) injecting a cobalt-aluminum mixed salt solution, a carbonate solution and an organic weak acid solution into a base solution in a parallel flow manner, and carrying out a co-precipitation reaction to obtain a precursor; and (2) stopping injection of the organic weak acid solution, continuing to inject the cobalt-aluminum mixed salt solution and the carbonate solution, and carrying out a co-precipitation reaction to obtain the high-aluminum doped cobalt carbonate. According to the method, through segmented coprecipitation and control of the types of precipitants used for coprecipitation of all the segments, the doping amount and uniformity of aluminum in cobalt carbonate can be improved, aluminum segregation is avoided, and meanwhile high-aluminum-doped cobalt carbonate higher in sphericity degree and better in compactness can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a high-aluminum-doped cobalt carbonate and a preparation method and application thereof. Background Art

[0002] With the rapid development of the new energy vehicle and portable electronic device industries, the performance requirements for lithium-ion batteries are increasing. Lithium cobalt oxide (LiCoO2), as a commonly used positive electrode material for lithium-ion batteries, has advantages such as high energy density and stable operating voltage, and occupies an important position in the field of consumer electronics. To further improve the comprehensive performance of lithium cobalt oxide, optimizing the material structure and electrochemical properties by doping with metal elements has become a research hotspot. Among them, aluminum doping can effectively improve the thermal stability, cycle performance and rate performance of lithium cobalt oxide. In the process of preparing high-aluminum-doped lithium cobalt oxide positive electrode materials, the performance of the high-aluminum-doped cobalt carbonate precursor plays a key role in the quality of the final product.

[0003] CN119591164A discloses a high-aluminum-doped basic cobalt carbonate and a preparation method thereof. The method comprises: 1) preparing a mixed solution using a cobalt salt and an aluminum salt; 2) adding a small amount of ammonium bicarbonate solution to a reaction kettle, turning on the heating, adding the mixed solution to the reaction kettle while stirring, controlling the pH, and reacting to obtain a seed crystal dispersion; 3) adding the mixed solution and ammonium bicarbonate solution to the seed crystal dispersion, controlling the pH, and continuing the reaction under heating and stirring until the particle size of the basic cobalt carbonate reaches a set value, stopping the reaction, filtering, washing, and drying to obtain a high-aluminum-doped basic cobalt carbonate.

[0004] CN119706962A discloses a composite aluminum-doped cobalt carbonate, its preparation method, and application. The preparation method comprises: preparing a first carbonate solution, a second carbonate solution, and an aluminum-doped cobalt salt solution; adding the aluminum-doped cobalt salt solution and the first carbonate solution to the second carbonate solution under stirring for a preliminary reaction to obtain a reaction solution containing cobalt carbonate seeds; and continuously adding the aluminum-doped cobalt salt solution and the first carbonate solution to the reaction solution for a first reaction and a second reaction, respectively, to obtain composite aluminum-doped cobalt carbonate particles.

[0005] The above scheme makes it difficult to obtain high-aluminum-doped cobalt carbonate particles with good sphericity. The irregular particle morphology will lead to poor dispersion of the material during the battery electrode coating process, affecting the uniformity and consistency of the electrode, and thus reducing the overall performance of the battery; on the other hand, in high-aluminum-doped cobalt carbonate, aluminum elements are prone to segregation, resulting in uneven distribution of aluminum elements inside and on the surface of the particles, resulting in unstable electrochemical properties of lithium cobalt oxide positive electrode materials, and unable to fully utilize the performance improvement advantages brought by aluminum doping, which limits the application of high-aluminum-doped lithium cobalt oxide in high-performance lithium-ion batteries. Summary of the Invention

[0006] The present invention aims to provide a high-aluminum-doped cobalt carbonate, a preparation method thereof, and an application thereof. The present invention uses segmented coprecipitation and controls the type of precipitant used in each segment of the coprecipitation to increase the aluminum doping amount and uniformity in the cobalt carbonate, avoid aluminum segregation, and simultaneously obtain a high-aluminum-doped cobalt carbonate with higher sphericity and better compactness. The aluminum doping in the cobalt tetroxide prepared by the high-aluminum-doped cobalt carbonate is highly uniform, the cobalt tetroxide has a good morphology, and although the aluminum doping amount is relatively high, it does not precipitate on the particle surface, resulting in higher electrical properties.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing high-aluminum-doped cobalt carbonate, the preparation method comprising the following steps:

[0009] (1) injecting a cobalt-aluminum mixed salt solution, a first precipitant solution, and a second precipitant solution into a bottom liquid in parallel, and obtaining a precursor through a first coprecipitation reaction;

[0010] (2) stopping the injection of the second precipitant solution, and continuing to inject the cobalt-aluminum mixed salt solution and the first precipitant solution, and obtaining the high-aluminum-doped cobalt carbonate through a second coprecipitation reaction;

[0011] The first precipitant solution includes a carbonate solution, and the second precipitant solution includes an organic weak acid solution.

[0012] During the first coprecipitation reaction and the second coprecipitation reaction of the present invention, the concentrations and flow rates of the injected cobalt-aluminum mixed salt solution and the first precipitant solution may be the same or different, and are not limited here.

[0013] In the preparation process of the high-aluminum-doped cobalt carbonate of the present invention, a carbonate solution and an organic weak acid solution are first introduced as a precipitant solution. The organic weak acid has a significant difference in the complexation of cobalt and aluminum. In the first coprecipitation process, the organic weak acid preferably combines with cobalt ions to form organic weak acid cobalt crystal nuclei, while aluminum has poor complexation ability and is more retained in the solution, delaying precipitation to form aluminum gradient doping and avoiding local enrichment. The carbonate solution provides CO3 2- Cobalt carbonate is generated, and the coprecipitation of the cobalt carbonate and the organic weak acid cobalt can achieve a specific precursor composition (such as a mixed anion structure). During the second coprecipitation reaction, the organic weak acid solution is stopped to avoid the continuous introduction of oxalate and the excessive generation of cobalt oxalate, thereby controlling the proportion of cobalt carbonate in the final product, improving the purity of the product, and reducing the risk of residual carbon. The alkaline environment of the carbonate promotes the formation of Al 3+By slowly coprecipitating in the form of Al(OH)3 or Al-doped cobalt carbonate and controlling the pH and carbonate concentration, the atomic-level dispersion of aluminum in the cobalt matrix can be achieved, reducing the phase separation caused by the precipitation of Al(OH)3 alone.

[0014] During the first coprecipitation process, the organic weak acid reacts with cobalt to form organic weak acid cobalt salts, which are mostly small needle-shaped or rod-shaped particles. They can serve as templates to guide the growth of cobalt carbonate and form more dense spherical or quasi-spherical particles (taking oxalic acid as an organic weak acid, the generated cobalt oxalate will undergo topological conversion with cobalt carbonate). High aluminum doping can easily lead to a decrease in the crystallinity of cobalt carbonate (Al 3+ Initially, the organic weak acid rapidly nucleates to form a highly crystalline organic weak acid cobalt core. Later, under the action of a carbonate solution, an Al-doped cobalt carbonate shell slowly grows, balancing the conflict between doping level and crystallinity. If an organic weak acid is used throughout the entire process, the CO2 and H2O produced by the decomposition of the organic weak acid cobalt may leave a porous structure during the calcination process to prepare cobalt trioxide.

[0015] Preferably, the molar concentration of cobalt ions in the cobalt-aluminum mixed salt solution in step (1) is 1.8 mol / L to 2 mol / L, for example, 1.8 mol / L, 1.85 mol / L, 1.9 mol / L, 1.95 mol / L or 2 mol / L, etc., but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0016] Preferably, the molar concentration of aluminum ions in the cobalt-aluminum mixed salt solution in step (1) is 40 mmol / L to 90 mmol / L, for example, 40 mmol / L, 50 mmol / L, 60 mmol / L, 70 mmol / L, 80 mmol / L or 90 mmol / L, etc., but is not limited to the listed values, and other values ​​not listed within this numerical range are also applicable.

[0017] Preferably, the solute of the first precipitant solution includes any one or a combination of at least two of ammonium carbonate, ammonium bicarbonate, sodium carbonate or potassium carbonate. Typical but non-limiting combinations include a combination of ammonium carbonate and ammonium bicarbonate, a combination of ammonium bicarbonate and sodium carbonate, or a combination of ammonium carbonate and potassium carbonate, etc., preferably ammonium carbonate and / or ammonium bicarbonate.

[0018] Preferably, the molar concentration of the first precipitant solution is 2 mol / L to 3 mol / L, for example, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L or 3 mol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the solute of the second precipitant solution includes any one of oxalic acid, citric acid or ethylenediaminetetraacetic acid, or a combination of at least two of them. Typical but non-limiting combinations include a combination of oxalic acid and citric acid, a combination of citric acid and ethylenediaminetetraacetic acid, or a combination of oxalic acid and ethylenediaminetetraacetic acid, etc., preferably oxalic acid.

[0020] Preferably, the molar concentration of the second precipitant solution is 0.5 mol / L to 1 mol / L, for example, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L, etc., and is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0021] Preferably, the base liquid includes a first precipitant.

[0022] Preferably, during the first coprecipitation reaction in step (1), the flow rate of the cobalt-aluminum mixed salt solution is 5 L / h to 10 L / h, for example: 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h or 10 L / h, etc., not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0023] Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first precipitant solution is 15 L / h to 20 L / h, for example: 15 L / h, 16 L / h, 17 L / h, 18 L / h, 19 L / h or 20 L / h, etc., not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0024] Preferably, during the first coprecipitation reaction in step (1), the flow rate of the second precipitant solution is 5 L / h to 10 L / h, for example: 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h or 10 L / h, etc., not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0025] Preferably, the pH of the first coprecipitation reaction in step (1) is 7.3 to 7.6, for example, 7.3, 7.35, 7.4, 7.5 or 7.6, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0026] Preferably, the temperature of the first coprecipitation reaction in step (1) is 30°C to 35°C, for example, 30°C, 32°C, 33°C, 34°C or 35°C, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 30°C to 32°C.

[0027] The high-aluminum-doped cobalt carbonate of the present invention is prepared at low temperature, which can significantly improve the uniformity of aluminum doping. Controlling the reaction temperature within the above range can ensure the uniformity of aluminum doping while avoiding aluminum segregation.

[0028] Preferably, stirring is performed during the first coprecipitation reaction in step (1).

[0029] Preferably, the stirring speed is 300 rpm to 500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, in the reaction system of the first coprecipitation reaction in step (1), the molar ratio of carbonate to cobalt ion is (3 to 3.5):1, for example: 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1 or 3.5:1, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] The present invention controls the precipitation rates of Co and Al by controlling the unit consumption of the first coprecipitation reaction (i.e., the molar ratio of carbonate to cobalt ions), so that Co and Al exist in the particles in a uniform state during the first coprecipitation, avoiding the generation of Al flakes or filaments, which affect the morphology of the later particles.

[0032] Preferably, the median particle size D50 of the precursor in step (1) is 1 μm to 2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, etc., and is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0033] Preferably, during the second coprecipitation reaction in step (2), the flow rate of the cobalt-aluminum mixed salt solution is 5 L / h to 10 L / h, for example: 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h or 10 L / h, etc., not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0034] Preferably, during the second coprecipitation reaction in step (2), the flow rate of the first precipitant solution is 10 L / h to 18 L / h, for example: 10 L / h, 11 L / h, 12 L / h, 13 L / h, 15 L / h or 18 L / h, etc., not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0035] Preferably, in step (2), the flow rate of the first precipitant solution during the second coprecipitation reaction is greater than the flow rate of the first precipitant solution during the first coprecipitation reaction.

[0036] Preferably, the pH of the second coprecipitation reaction in step (2) is 7.2 to 7.4, for example, 7.2, 7.25, 7.3, 7.35 or 7.4, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0037] The pH of the first coprecipitation reaction and the second coprecipitation reaction of the present invention is controlled by the flow rate of the precipitant. During the second coprecipitation reaction, the flow rate of the first precipitant solution is greater than the flow rate of the first precipitant solution of the first coprecipitation reaction, while the flow rate of the cobalt-aluminum mixed salt solution remains unchanged, thereby causing the pH of the second coprecipitation reaction to be slightly lower than the pH of the first coprecipitation reaction.

[0038] Preferably, the temperature of the second coprecipitation reaction in step (2) is 30°C to 35°C, for example, 30°C, 32°C, 33°C, 34°C or 35°C, etc., not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 30°C to 32°C.

[0039] Preferably, stirring is performed during the second coprecipitation reaction in step (2).

[0040] Preferably, the stirring speed is 300 rpm to 500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm.

[0041] Preferably, in the reaction system of the second coprecipitation reaction in step (2), the molar ratio of carbonate to cobalt ion is (2.5-2.7):1, for example: 2.5:1, 2.55:1, 2.6:1, 2.65:1 or 2.7:1, etc., and is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0042] The present invention controls the unit consumption of the second coprecipitation reaction (i.e., the molar ratio of carbonate to cobalt ions) to maintain a relatively high unit consumption. The second coprecipitation morphology continues the morphology of the first coprecipitation. Compared with the first coprecipitation reaction, the unit consumption of the second coprecipitation is reduced, but it is also at a relatively high unit consumption to ensure that Co and Al are present in a uniform state and that the particles do not exhibit Co and Al phase separation.

[0043] Preferably, the median particle size D50 of the high aluminum-doped cobalt carbonate in step (2) is 4 μm to 5 μm, for example, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm or 5 μm, etc., and is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0044] In a second aspect, the present invention provides a high-aluminum-doped cobalt carbonate, which is prepared by the preparation method described in the first aspect.

[0045] Preferably, based on the mass of cobalt in the high-aluminum-doped cobalt carbonate being 100%, the mass of the aluminum element in the high-aluminum-doped cobalt carbonate is 1% to 2.2%, for example, 1%, 1.2%, 1.5%, 1.8% or 2.2%, etc., and is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0046] In a third aspect, the present invention provides a high-aluminum-doped cobalt oxide, which is prepared by calcining the high-aluminum-doped cobalt carbonate as described in the second aspect.

[0047] Preferably, the calcination temperature is 550°C to 650°C, for example, 550°C, 580°C, 600°C, 620°C or 650°C, etc., and is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0048] Preferably, hot water washing and drying treatment are performed before calcination.

[0049] In a fourth aspect, the present invention provides a lithium cobalt oxide positive electrode material, which is prepared by mixing and sintering the high-aluminum-doped cobalt tetroxide as described in the third aspect with a lithium source.

[0050] Preferably, the lithium source comprises lithium hydroxide and / or lithium carbonate.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The present invention can improve the aluminum doping amount and uniformity in cobalt carbonate and avoid aluminum segregation by staged coprecipitation and controlling the type of precipitant used in each stage of coprecipitation. At the same time, a high-aluminum-doped cobalt carbonate with higher sphericity and better density can be obtained. The aluminum doping in the cobalt tetroxide prepared by the high-aluminum-doped cobalt carbonate is highly uniform, and the cobalt tetroxide has a good morphology. Although the aluminum doping amount is high, it will not precipitate on the particle surface, so that it has higher electrical properties.

[0053] (2) The surface of the aluminum-doped cobalt tetroxide made using the high-aluminum-doped cobalt carbonate of the present invention has only slight aluminum segregation, and the first discharge specific capacity of the battery made using the lithium cobalt oxide made from the high-aluminum-doped cobalt carbonate of the present invention as the positive electrode material can reach more than 180 mAh / g, and the capacity retention rate can reach more than 70%. By adjusting the preparation conditions, the surface of the aluminum-doped cobalt tetroxide made using the high-aluminum-doped cobalt carbonate of the present invention can avoid aluminum segregation, and the first discharge specific capacity of the battery made using the lithium cobalt oxide made from the high-aluminum-doped cobalt carbonate of the present invention as the positive electrode material can reach more than 190 mAh / g, and the capacity retention rate can reach more than 81%. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a SEM image of the high-aluminum-doped cobalt carbonate provided in Example 1 of the present invention.

[0055] Figure 2 This is an SEM image of the high aluminum-doped cobalt carbonate provided in Comparative Example 1.

[0056] Figure 3 This is an SEM image of the high-aluminum-doped cobalt carbonate provided in Comparative Example 2. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Example 1

[0059] This embodiment provides a high-aluminum-doped cobalt carbonate, and the preparation method of the high-aluminum-doped cobalt carbonate is as follows:

[0060] (1) preparing a sulfate cobalt aluminum mixed salt solution with an aluminum concentration of 57 mmol / L and a cobalt concentration of 1.866 mol / L, a 2.78 mol / L ammonium bicarbonate solution, a 0.8 mol / L oxalic acid solution, and a 2.78 mol / L ammonium bicarbonate solution as a bottom solution, controlling the sulfate cobalt aluminum mixed salt solution, the ammonium bicarbonate solution, and the oxalic acid solution to flow into the bottom solution at flow rates of 8 L / h, 17 L / h, and 8 L / h, respectively, at 31° C. and a stirring speed of 400 rpm, controlling the pH to 7.5 for a first coprecipitation reaction, controlling the unit consumption (i.e., the molar ratio of carbonate to cobalt ions) to 3.2:1, until the median particle size D50 of the particles in the system is 1.5 μm, stopping the reaction, and obtaining a precursor;

[0061] (2) Stop feeding the oxalic acid solution, keep the feed rates of the cobalt-aluminum sulfate mixed salt solution and the ammonium bicarbonate solution unchanged, and carry out a second coprecipitation reaction at 31° C. and a stirring speed of 400 rpm, controlling the pH to 7.3, and controlling the unit consumption to 2.6:1 until the median particle size D50 of the particles in the system reaches 4.5 μm, and then stop the reaction to obtain the high-aluminum-doped cobalt carbonate.

[0062] Based on the mass of cobalt in the high-aluminum-doped cobalt carbonate being 100%, the mass of aluminum in the high-aluminum-doped cobalt carbonate is 1.39%.

[0063] The SEM image of the high aluminum doped cobalt carbonate is as follows Figure 1 shown.

[0064] Example 2

[0065] This embodiment provides a high-aluminum-doped cobalt carbonate, and the preparation method of the high-aluminum-doped cobalt carbonate is as follows:

[0066] (1) preparing a sulfate cobalt aluminum mixed salt solution with an aluminum concentration of 40 mmol / L and a cobalt concentration of 1.8 mol / L, a 2 mol / L ammonium bicarbonate solution, a 1 mol / L citric acid solution, and a 2 mol / L ammonium carbonate solution as a bottom solution, controlling the sulfate cobalt aluminum mixed salt solution, the ammonium carbonate solution, and the citric acid solution to flow into the bottom solution at flow rates of 5 L / h, 15 L / h, and 5 L / h, respectively, at 32° C. and a stirring speed of 300 rpm, controlling the pH to be 7.6 to perform a first coprecipitation reaction (unit consumption, i.e., a molar ratio of carbonate to cobalt ions = 3.3:1) until the median particle size D50 of the particles in the system is 1 μm, stopping the reaction, and obtaining a precursor;

[0067] (2) Stop feeding the citric acid solution, keep the feeding rate of the cobalt-aluminum sulfate mixed salt solution unchanged, and feed the ammonium carbonate solution at a rate of 12 L / h. At 32° C. and a stirring speed of 300 rpm, control the pH to 7.4 and conduct a second coprecipitation reaction (unit consumption = 2.67:1) until the median particle size D50 of the particles in the system reaches 4 μm. Stop the reaction to obtain the high-aluminum-doped cobalt carbonate.

[0068] Based on the mass of cobalt in the high-aluminum-doped cobalt carbonate being 100%, the mass of aluminum in the high-aluminum-doped cobalt carbonate is 1.04%.

[0069] Example 3

[0070] This embodiment provides a high-aluminum-doped cobalt carbonate, and the preparation method of the high-aluminum-doped cobalt carbonate is as follows:

[0071] (1) preparing a sulfate cobalt aluminum mixed salt solution with an aluminum concentration of 90 mmol / L and a cobalt concentration of 2 mol / L, a 3 mol / L ammonium bicarbonate solution, a 0.5 mol / L oxalic acid solution, and a 3 mol / L ammonium bicarbonate solution as a bottom solution, controlling the sulfate cobalt aluminum mixed salt solution, the ammonium bicarbonate solution, and the oxalic acid solution to flow into the bottom solution at flow rates of 10 L / h, 20 L / h, and 10 L / h, respectively, at 30° C. and a stirring speed of 500 rpm, controlling the pH to 7.3, and performing a first coprecipitation reaction (unit consumption = 3:1) until the median particle size D50 of the particles in the system is 2 μm, stopping the reaction, and obtaining a precursor;

[0072] (2) Stop feeding the oxalic acid solution, keep the feeding rate of the cobalt-aluminum sulfate mixed salt solution unchanged, and feed the ammonium bicarbonate solution at a rate of 18 L / h. At 30° C. and a stirring speed of 500 rpm, control the pH to 7.2 and conduct a second coprecipitation reaction (unit consumption = 2.7:1) until the median particle size D50 of the particles in the system reaches 4 μm. Stop the reaction to obtain the high-aluminum-doped cobalt carbonate.

[0073] Based on the mass of cobalt in the high-aluminum-doped cobalt carbonate being 100%, the mass of aluminum in the high-aluminum-doped cobalt carbonate is 2.05%.

[0074] Example 4

[0075] The only difference between this embodiment and embodiment 1 is that the pH in step (1) is 7.2, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0076] Example 5

[0077] The only difference between this embodiment and embodiment 1 is that the pH in step (1) is 7.8, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0078] Example 6

[0079] The only difference between this embodiment and embodiment 1 is that the pH in step (2) is 7.1, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0080] Example 7

[0081] The only difference between this embodiment and embodiment 1 is that the pH in step (2) is 7.5, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0082] Comparative Example 1

[0083] The only difference between this comparative example and Example 1 is that step (2) is also the same as step (1) in that the oxalic acid solution of the same concentration is passed through at the same flow rate, and the other conditions and parameters are exactly the same as those in Example 1.

[0084] The SEM image of the obtained high aluminum doped cobalt carbonate is as follows Figure 2 shown.

[0085] Comparative Example 2

[0086] The only difference between this comparative example and Example 1 is that oxalic acid solution is not introduced in step (1), and the other conditions and parameters are exactly the same as those in Example 1.

[0087] The SEM image of the obtained high aluminum doped cobalt carbonate is as follows Figure 3 shown.

[0088] Performance testing:

[0089] The high-aluminum-doped cobalt carbonate prepared in the Examples and Comparative Examples was calcined at 640°C for 90 minutes to obtain high-aluminum-doped cobalt tetroxide. The high-aluminum-doped cobalt tetroxide was ball-milled with lithium carbonate at a cobalt-to-lithium molar ratio of 1:1.05, and calcined at 800°C for 8 hours in an air atmosphere. After crushing and screening, a lithium cobalt oxide positive electrode material was obtained. This lithium cobalt oxide was used as the positive electrode material, and a metal lithium sheet was used as the negative electrode. A button cell was assembled and charge-discharge tests were performed. The test results are shown in Table 1:

[0090] Table 1

[0091]

[0092] As can be seen from Table 1, it can be obtained from Examples 1-7 that the surface of the aluminum-doped cobalt oxide made using the high-aluminum-doped cobalt carbonate of the present invention has only slight aluminum segregation, and the first discharge specific capacity of the battery made using the lithium cobalt oxide made from the high-aluminum-doped cobalt carbonate of the present invention as the positive electrode material can reach more than 180 mAh / g, and the capacity retention rate can reach more than 70%. By adjusting the preparation conditions, the surface of the aluminum-doped cobalt oxide made using the high-aluminum-doped cobalt carbonate of the present invention can avoid aluminum segregation, and the first discharge specific capacity of the battery made using the lithium cobalt oxide made from the high-aluminum-doped cobalt carbonate of the present invention as the positive electrode material can reach more than 190 mAh / g, and the capacity retention rate can reach more than 81%.

[0093] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the high-aluminum-doped cobalt carbonate of the present invention, the pH of the first coprecipitation reaction will affect its performance. The pH of the first coprecipitation reaction is controlled at 7.5-8, and the performance of the high-aluminum-doped cobalt carbonate obtained is better. If the pH of the first coprecipitation reaction is too low, segregation will occur and the Al segregation will be difficult to eliminate in the later stage of the morphology. If the pH of the first coprecipitation reaction is too high, aluminum will precipitate during the washing and calcination process, affecting the electrical properties.

[0094] By comparing Example 1 with Examples 6-7, it can be seen that during the preparation process of the high-aluminum-doped cobalt carbonate of the present invention, the pH of the second coprecipitation reaction affects its performance. When the pH of the second coprecipitation reaction is controlled at 8 to 8.5, the performance of the high-aluminum-doped cobalt carbonate obtained is better. If the pH of the second coprecipitation reaction is too low, Al will precipitate, thereby affecting the performance. If the pH of the second coprecipitation reaction is too high, nuclear explosion will occur during the reaction period, and aluminum will precipitate after washing and calcination, affecting the electrical properties.

[0095] From the comparison between Example 1 and Comparative Example 1, it can be seen that if oxalic acid is used throughout the process, part of Al 3+ It may remain in the mother liquor due to incomplete precipitation, reducing the efficiency of aluminum doping. Oxalate ions are prone to produce residual carbon during calcination, affecting the electrical properties of the material (such as conductivity). Discontinuing the use of oxalic acid in the later stage can reduce the introduction of carbon sources, especially for high aluminum systems (Al 3+may catalyze the oxidation of carbon residues) is more critical.

[0096] By comparing Example 1 and Comparative Example 2, it can be seen that during the first coprecipitation process, the organic weak acid (oxalic acid) reacts with cobalt to form organic weak acid cobalt salts, which are mostly small needle-shaped or rod-shaped particles, which can serve as a template to guide the growth of cobalt carbonate to form more dense spherical or quasi-spherical particles (taking oxalic acid as an organic weak acid as an example, the generated cobalt oxalate will undergo topological conversion with cobalt carbonate). High aluminum doping can easily lead to a decrease in the crystallinity of cobalt carbonate (Al 3+ In the early stage, the organic weak acid rapidly nucleates to form a highly crystalline organic weak acid cobalt core, and in the later stage, the Al-doped cobalt carbonate shell slowly grows under the action of the carbonate solution, which can balance the contradiction between the doping amount and the crystallinity.

[0097] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A method for preparing high-aluminum-doped cobalt carbonate, characterized in that: The preparation method comprises the following steps: (1) injecting a cobalt-aluminum mixed salt solution, a first precipitant solution, and a second precipitant solution into a bottom liquid in parallel, and obtaining a precursor through a first coprecipitation reaction; (2) stopping the injection of the second precipitant solution, and continuing to inject the cobalt-aluminum mixed salt solution and the first precipitant solution, and obtaining the high-aluminum-doped cobalt carbonate through a second coprecipitation reaction; The first precipitant solution includes a carbonate solution, and the second precipitant solution includes an organic weak acid solution.

2. The preparation method according to claim 1, wherein The molar concentration of cobalt ions in the cobalt-aluminum mixed salt solution in step (1) is 1.8 mol / L to 2 mol / L; Preferably, the molar concentration of aluminum ions in the cobalt-aluminum mixed salt solution in step (1) is 40 mmol / L to 90 mmol / L; Preferably, the solute of the first precipitant solution comprises any one or a combination of at least two of ammonium carbonate, ammonium bicarbonate, sodium carbonate or potassium carbonate, preferably ammonium carbonate and / or ammonium bicarbonate; Preferably, the molar concentration of the first precipitant solution is 2 mol / L to 3 mol / L; Preferably, the solute of the second precipitant solution comprises any one of oxalic acid, citric acid or ethylenediaminetetraacetic acid or a combination of at least two thereof, preferably oxalic acid; Preferably, the molar concentration of the second precipitant solution is 0.5 mol / L to 1 mol / L; Preferably, the base liquid includes a first precipitant.

3. The preparation method according to claim 1 or 2, wherein During the first coprecipitation reaction in step (1), the flow rate of the cobalt-aluminum mixed salt solution is 5 L / h to 10 L / h; Preferably, during the first coprecipitation reaction in step (1), the flow rate of the first precipitant solution is 15 L / h to 20 L / h; Preferably, during the first coprecipitation reaction in step (1), the flow rate of the second precipitant solution is 5 L / h to 10 L / h; Preferably, the pH of the first coprecipitation reaction in step (1) is 7.3 to 7.6; Preferably, the temperature of the first coprecipitation reaction in step (1) is 30°C to 35°C, preferably 30°C to 32°C; Preferably, stirring is performed during the first coprecipitation reaction in step (1); Preferably, the stirring speed is 300 rpm to 500 rpm; Preferably, in the reaction system of the first coprecipitation reaction in step (1), the molar ratio of carbonate to cobalt ions is (3-3.5):

1.

4. The preparation method according to any one of claims 1 to 3, wherein The median particle size D50 of the precursor in step (1) is 1 μm to 2 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that During the second coprecipitation reaction in step (2), the flow rate of the cobalt-aluminum mixed salt solution is 5 L / h to 10 L / h; Preferably, during the second coprecipitation reaction in step (2), the flow rate of the first precipitant solution is 10 L / h to 18 L / h; Preferably, the pH of the second coprecipitation reaction in step (2) is 7.2 to 7.4; Preferably, the temperature of the second coprecipitation reaction in step (2) is 30°C to 35°C, preferably 30°C to 32°C; Preferably, stirring is performed during the second coprecipitation reaction in step (2); Preferably, the stirring speed is 300 rpm to 500 rpm; Preferably, in the reaction system of the second coprecipitation reaction in step (2), the molar ratio of carbonate to cobalt ions is (2.5-2.7):

1.

6. The preparation method according to any one of claims 1 to 5, characterized in that The median particle size D50 of the high aluminum-doped cobalt carbonate in step (2) is 4 μm to 5 μm.

7. A high aluminum-doped cobalt carbonate, characterized in that: The high aluminum-doped cobalt carbonate is prepared by the preparation method according to any one of claims 1 to 6.

8. The high aluminum-doped cobalt carbonate according to claim 7, characterized in that Taking the mass of cobalt in the high-aluminum-doped cobalt carbonate as 100%, the mass of aluminum element in the high-aluminum-doped cobalt carbonate is 1% to 2.2%.

9. A high aluminum doped cobalt oxide, characterized in that: The high-aluminum-doped cobalt tetroxide is prepared by calcining the high-aluminum-doped cobalt carbonate as claimed in claim 7 or 8.

10. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide positive electrode material is prepared by mixing and sintering the high aluminum-doped cobalt tetroxide as claimed in claim 9 with a lithium source.

Citation Information

Patent Citations

  • Alkali cobalt carbonate with high aluminum doping amount and preparation method thereof

    CN119591164A

  • Composite-form aluminum-doped cobalt carbonate as well as preparation method and application thereof

    CN119706962A

Cited By

  • Method for improving surface uniformity of aluminum-doped cobalt carbonate, aluminum-doped cobalt carbonate and application of aluminum-doped cobalt carbonate

    CN121449114A